High-Strength Albumin Hydrogels With Hybrid Cross-Linking - Lu, Shaoping; Zhu, Lin; Wang, Qilin; Liu, Zhao; Tang, Chen; Sun, Huan; Yang, Jia; Qin, Gang; Sun, Gengzhi; Chen, Qiang (Frontiers in Chemistry, 2020)
Natural protein-based hydrogels possess excellent biocompatibility, however, most of them are weak or brittle. In the present of work, high strength hybrid dual-crosslinking BSA gels (BSA DC gels), consisting of chemical cross-linking and physical cross-linking, were fabricated by a facile photoreaction-heating process. BSA DC gels appeared high transparence (light transmittance of ~90%) and high strength. At optimal condition, BSA DC gel exhibited high compressive strength (σc,f) of 37.81±2.61 MPa and tensile strength (σt,f) of 0.62±0.078 MPa, which was much stronger than physically cross-linked BSA gel (BSA PC gel) and chemically cross-linked BSA gel (BSA CC gel). More importantly, BSA DC gel displayed non-swelling properties in DI water, pH = 3.0 and pH = 10.0, which maintained high strength. Moreover, BSA DC gel also demonstrated large hysteresis, rapid self-recovery and excellent fatigue resistance properties. It is believed our BSA DC gel can be potentially applied in biomedical fields.